Constructs from the Consolidated Framework for Implementation Research associated with church enrollment and intervention adoption in a national implementation study of a faith-based organizational change intervention - Sara Wilcox; Ruth P. Saunders; Andrew T. Kaczynski; A. Caroline Rudisill; Jessica Stucker; Deborah Kinnard; Brooke W. McKeever; Kelsey R. Day; Jasmin Parker-Brown; Ye Sil Kim (BMC, 2024)
Abstract Background Organizational adoption is a key but understudied step in translating evidence-based interventions into practice. The purpose of this study was to report recruitment strategies and factors associated with church enrollment and intervention adoption in a national implementation study of the Faith, Activity, and Nutrition (FAN) program. Methods We worked with partners using multiple strategies to disseminate intervention availability. Interested churches completed an online form. To enroll, the church coordinator (FAN coordinator) and pastor completed baseline surveys and then received intervention online training access. We compared enrolled vs. non-enrolled churches on how they heard about the study and church characteristics. We compared intervention-adopting vs. non-adopting churches on Consolidated Framework for Implementation Research (CFIR) constructs using Fisher's exact tests, χ2, or independent sample t-tests and reported differences where p < 0.10, d≥|0.35|, or the difference in percentage points was ≥ 10. Results We received 226 interest forms; 107 churches enrolled, and 85 churches adopted the intervention. Faith-based sources were the most, and paid media the least, effective in reaching churches, which were largely from the southeast with a Methodist or Baptist tradition (no differences by enrollment status). Enrolled churches were less likely to have 500 + worshipers and more likely to have attended a study information session than non-enrolled churches. Church (CFIR inner setting) and FAN coordinator characteristics, but not intervention characteristics, were related to intervention adoption. Conclusion Partnerships, relationships, and "face time" are important for enrolling churches in evidence-based interventions. Church and church coordinator characteristics are related to intervention adoption. Further work on adoption conceptualization and operationalization is needed.